2018
DOI: 10.1111/1747-0080.12474
|View full text |Cite
|
Sign up to set email alerts
|

Complementary feeding: Attitudes, knowledge and practices of urban families in northern Thailand

Abstract: These findings suggest that nutritional education should be extended to all caregivers involved in CF to improve the adherence to feeding recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
1
20
0
2
Order By: Relevance
“…Introducing nontraditional food and adopting unfamiliar feeding practices may be a cause of argument in some families. The different attitude and knowledge gaps between mothers and other family members were also found in another study (Kittisakmontri et al, 2019). Narrowing these gaps is needed to create a supportive environment.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Introducing nontraditional food and adopting unfamiliar feeding practices may be a cause of argument in some families. The different attitude and knowledge gaps between mothers and other family members were also found in another study (Kittisakmontri et al, 2019). Narrowing these gaps is needed to create a supportive environment.…”
Section: Discussionsupporting
confidence: 72%
“…During early childhood, parents' feeding practices influence children's health and weight status. While feeding practices play a key role promoting children's health, previous research has found that Thai parents have inappropriate child feeding beliefs and practices, such as inadequate food diversity, and the early introduction of complementary foods and seasonings (Joshi et al, 2012; Kittisakmontri, Fewtrell, Roekworachai, Phanpong, & Lanigan, 2019; Roesler, Smithers, Winichagoon, Wangpakapattanawong, & Moore, 2018). The early introduction of rice and water is also the common reason of failure of exclusive breastfeeding (Winichagoon, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, we decided to adopt a sequential approach in 3 consecutive studies, beginning with a descriptive study to gather information on the attitudes, knowledge, and practices related to complementary feeding in Thai families. This study provided a clearer picture of complementary feeding among Thai parents and highlighted interesting findings that were used in the design of the current prospective cohort study [ 39 ]. For example, rice porridge and mashed banana were the most common first foods for Thai infants with or without a small amount of egg yolk.…”
Section: Discussionmentioning
confidence: 99%
“…If a mother has good or positive attitudes towards the provision of complementary feeding, the behavior in selecting the type of complementary feeding to be given to her baby will also be good or positive. In this case, this mother will choose the right type of complementary feeding that is complete in macro and micro-nutrient composition, so that the nutritional needs of the baby can be fulfilled (Kittisakmontri, Fewtrell, Roekworachai, Phanpong, & Lanigan, 2018). There are many factors that influence mothers' attitudes in selecting complementary feedings, including experience, cultural influences, religion and the influence of others (Yeganeh et al, 2018).…”
Section: Factors Associated With Mothers' Behavior In Selecting Complementary Feedingmentioning
confidence: 99%